Production risk of organic rice due to climate change in Magelang Regency, Central Java, Indonesia - Istiyanti Eni; Widowati Indah; Al Hasan Thohari (BIO Web of Conferences)
Organic rice farming is a rice cultivation activity applies ecological principles without using chemical fertilizers and pesticides. The big challenge for organic rice farming is climate change in the form of high temperatures, drought, high rainfall which is difficult to predict. This situation have an impact on decline in production and income of organic rice farming. The objective of the study was to determine the income organic rice farming and analyzes the levels and factors affecting production risk of organic rice. The study was conducted in Magelang Regency with consideration that is a pilot project for organic rice farming in Indonesia and have farmer groups received organic certification. Respondents consisted of 75 organic rice farmers selected using simple random sampling methods. The data was taken through interviews based on questionnaires and documentation methods. Production risks were analyzed using the coefficient of variation and factors that influence production risk were analyzed using the Cobb-Douglass production function with Just and Pope approach. The results showed that the income of organic rice farming on an average land area of 3,690 m2 was IDR 6,694,860. Organic rice farming has a low production risk category. Factors that affect the production risk are land area and labor.